2022
DOI: 10.3390/en15062035
|View full text |Cite
|
Sign up to set email alerts
|

Active Power Control to Mitigate Frequency Deviations in Large-Scale Grid-Connected PV System Using Grid-Forming Single-Stage Inverters

Abstract: Over the last few years, the number of grid-connected photovoltaic systems (GCPVS) has expanded substantially. The increase in GCPVS integration may lead to operational issues for the grid. Thus, modern GCPVS control mechanisms should be used to improve grid efficiency, reliability, and stability. In terms of frequency stability, conventional generating units usually have a governor control that regulates the primary load frequency in cases of imbalance situations. This control should be activated immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The results indicated that the Beta distribution was better (RMSE=0.042308). This is depicted by Figure (7). To ascertain the optimal parameter settings for this particular design strategy, we adopt the same methodology outlined in the study by [1], wherein diverse class parameters are evaluated through a statistical analysis of solutions.…”
Section: The Monte-carlo Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that the Beta distribution was better (RMSE=0.042308). This is depicted by Figure (7). To ascertain the optimal parameter settings for this particular design strategy, we adopt the same methodology outlined in the study by [1], wherein diverse class parameters are evaluated through a statistical analysis of solutions.…”
Section: The Monte-carlo Methodsmentioning
confidence: 99%
“…This is due to the intermittency, non-dispatchable nature of the SPV power, and excessive applications of electronic devices such as inverters and converters [1,5,6]. Among these technical impacts, Total Harmonic Distortion (THD) seems to be a fast-growing challenge for power quality [2,7]. According to various studies, including [7,8], extensive utilization of power electronics devices (inverter-based interfaces) gives rise to current and voltage harmonics, which initiate additional transformers and generators core losses as well as transmission losses for conductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, renewable energy sources have been used to control active and reactive power outputs using existing technologies and strategies [32][33][34][35][36][37]. However, the existing operational renewable energy sources in South Korea do not require this function at the time of connection.…”
Section: Inertia and Non-synchronous Generationmentioning
confidence: 99%
“…A decrease in system inertia degrades the frequency stability by increasing the rate of change of frequency (RoCof) and degrading the frequency nadir [31]. Recently, renewable energy sources have been used to control active and reactive power outputs using existing technologies and strategies [32–37]. However, the existing operational renewable energy sources in South Korea do not require this function at the time of connection.…”
Section: Non‐synchronous Generation In South Koreamentioning
confidence: 99%